Cauchy-Dirichlet problem for the nonlinear degenerate parabolic equations - Ismail Kombe (Abstract and Applied Analysis)
We will investigate the nonexistence of positive solutions for the following nonlinear parabolic partial differential equation: ∂u/∂t=ℒu+V(w)up−1 in Ω×(0,T), 1<p<2, u(w,0)=u0(w)≥0 in Ω, u(w,t)=0 on ∂Ω×(0,T) where ℒ is the subelliptic p-Laplacian and V∈Lloc1(Ω).